2020
DOI: 10.3844/ajbbsp.2020.280.287
|View full text |Cite
|
Sign up to set email alerts
|

Distribution Pattern of SN in Qinghai-Tibet Plateau and Its Relationship with Environmental Factors

Abstract: Studying the distribution pattern and driving mechanism of Soil Nitrogen (SN) in the agricultural areas of the Qinghai-Tibet Plateau is of certain significance for the rational use of N fertilizer, improving the quality of land use and protecting the environment. The SN content of cultivated soil in Qinghai-Tibet Plateau agricultural areas was analyzed by combining geographical and meteorological factors. It was found that the average Soil Total N (STN) in farmland was 2.4690 g/kg, which was the first class st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
1
0
0
Order By: Relevance
“…At the beginning of the study, field investigation of Ambrosia trifida distribution points also confirmed this conclusion, Ambrosia trifida is mostly distributed in cultivated land, both sides of roads, both sides of rivers, and so on, which is consistent with the field survey results of Ma Qianqian et al on Ambrosia trifida [30]. At the same time, Huang Qiaoqiao et al [31] also pointed out that human activities have a significant role in promoting the spread and distribution of alien invasive plants, whether on a large-scale or a small-scale, its impact is also higher than the natural environmental factors [32]. In addition to the human factors, the temperature and humidity factors in this study also have an important impact on the distribution and diffusion of Ambrosia trifida.…”
Section: The Dominant Environmental Variable Limiting the Distributio...supporting
confidence: 82%
“…At the beginning of the study, field investigation of Ambrosia trifida distribution points also confirmed this conclusion, Ambrosia trifida is mostly distributed in cultivated land, both sides of roads, both sides of rivers, and so on, which is consistent with the field survey results of Ma Qianqian et al on Ambrosia trifida [30]. At the same time, Huang Qiaoqiao et al [31] also pointed out that human activities have a significant role in promoting the spread and distribution of alien invasive plants, whether on a large-scale or a small-scale, its impact is also higher than the natural environmental factors [32]. In addition to the human factors, the temperature and humidity factors in this study also have an important impact on the distribution and diffusion of Ambrosia trifida.…”
Section: The Dominant Environmental Variable Limiting the Distributio...supporting
confidence: 82%